Traders women at Makkah and Medina in the early of Islam - Karim, Mohamed Shams El Din (Journal of Islamic Sciences, 2019)
This study aims at shedding light on the role and activity of women in trade in Makkah and Medina in the early of Islam. It should be noted that the follower, reader and researcher in the affairs of Islamic studies in general, and historical studies in particular, find in the political system and Islamic law at the time, It stands against the aspirations of Arab Muslim women and prevents them from moving forward towards self-realization, and in the course of trade or any other activity. On the contrary, we found through this study there is great support by those who are responsible for the affairs of the emerging Islamic state at the time, Same and me Its role and ability to participate effectively in society.Thus, we note previously through research and study and careful reading of the historical sources and historical jurisprudence, in which historians cited many accounts of the role of Arab Muslim women and their active participation in the commercial activity in Mecca and Medina, and despite the low participation of women in trade, In the society, through the competition with men and in a difficult field, where we find the hardship of travel and travel between the markets and stand with the item with them, and has the ability to practice the sale and purchase, as well as speculation with money with men, and they were traveling to markets to bring the most Among the people, and thus managed to Arab Muslim women to match men, and note some of them have supported their husbands in meeting the requirements of daily life and provide a good living in a difficult and harsh environment, and historians have written in their writings the emergence of markets for women in Medina, Al-Shattaab (may Allaah be pleased with him) used Al-Shifa 'bint Abdullah on these markets as an accountant to monitor what is going on in them, and it was her duty to monitor the scales and scales so that there would be no cheating.The most important findings of the study:• The study showed the role of women and they play all the vital roles and participation of their Muslim brothers and are the cause of the rise of civilizational society, through its use as a worker responsible for the market and highlighting its role and ability to perform the tasks entrusted to it in the best picture.• The location of the Arabian Peninsula, which mediates the ancient world and opens up to Yemen, Iraq, Persia, Syria and Egypt, and at the same time overlooking the waters of the Shatt al-Arab, the Red Sea, the Arabian Sea and the Gulf of Aden, has had a significant impact on the revitalization of trade.
Keywords: Women; Trade; Early of Islam; Makkah; Medina